PENGARUH SELF DIRECTED LERANING DAN KEDISIPLINAN SISWA TERHADAP HASIL BELAJAR BAHASA INGGRIS KELAS VIII SMP NEGERI I SUNGAI LALA KABUPATEN INDRAGIRI HULU - Eton, Eton; Alim, Jesi Alexander; Ardiasih, Lidwina Sri (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2023)
This study aims to find out the influence of student learning independence and discipline on the results of learning English class VIII SMP Negeri 1 Sungai Lala Kabupaten Indragiri Hulu. This research used a quantitative approach of associative type of research. The data analysis technique used multiple linear analysis. The results of the study obtained a calculated F value of 67,673 > Ftabel of 3,099 and the result of a Sig. value is 0.000 < 0.05, it can be concluded that there is a significant influence between Student Independence (X1) and Learning Discipline (X2) on English Learning Outcomes of Class VIII Students of SMP Negeri 1 Sungai Lala, Indragiri Hulu Regency (Y). Based on the results of the coefficient of determination, the result of R Square was 60.3%. This shows that the two free variables consisting of Student Independence and Learning Discipline contributed to influencing student English learning outcomes by 60.37%. Based on this, it is concluded that the better the Student Independence and Learning Discipline, the better the English Learning Outcomes of Class VIII Students of SMP Negeri 1 Sungai Lala, Indragiri Hulu Regency.